Election night Bruce Bronzan Victory for District 3 Supervisor - Watkins, Howard K. (1976)
Bruce Bronzan happily watching television report, Doug Broten photographing Howard Watkins taking photograph ,Robert Quesada and Molly Miles on left; Carol Kalkowski, Doug Jones, Gerre Gurland-Jones